2019
DOI: 10.1016/j.bpsc.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Classification Accuracy of Neuroimaging Biomarkers in Attention-Deficit/Hyperactivity Disorder: Effects of Sample Size and Circular Analysis

Abstract: High classification accuracies in neuroimaging studies of ADHD appear to be inflated by circular analysis and small sample size. Accuracies on independent datasets were consistent with known heterogeneity of the disorder. Steps to resolve these issues, and a shift toward accounting for sample heterogeneity and prediction of future outcomes, will be crucial in future classification studies in ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
68
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 107 publications
2
68
2
1
Order By: Relevance
“…Recently, machine learning algorithms have used EEG spectral power, including TBR, to generate classification models that distinguish between childhood ADHD and neuro-typical controls (31). In adults, studies report 68% accuracy for relative theta power (32) and 76% accuracy for power in all frequency bands (18).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, machine learning algorithms have used EEG spectral power, including TBR, to generate classification models that distinguish between childhood ADHD and neuro-typical controls (31). In adults, studies report 68% accuracy for relative theta power (32) and 76% accuracy for power in all frequency bands (18).…”
Section: Introductionmentioning
confidence: 99%
“…In adults, studies report 68% accuracy for relative theta power (32) and 76% accuracy for power in all frequency bands (18). However, Pulini et al (31) concluded that methodological factors can lead to inflated accuracy estimates in machine-learning studies using neuroimaging data to classify ADHD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 300 study by Tamboer and colleagues (2016), classification performance dropped to around 60% 301 when the trained classifier was applied to an independent sample. We only performed 302 classification within the available dataset and it would be important to assess the current 303 classifier's performance within additional datasets (Pulini et al 2018). In addition, to further 304 advance on the relation between EEG network features and cognitive deficits in dyslexia, 305 longitudinal studies should examine whether the current approach could be used to predict 306 reading improvements or treatment outcomes.…”
mentioning
confidence: 99%